2005
DOI: 10.1038/sj.ijo.0803157
|View full text |Cite
|
Sign up to set email alerts
|

Image quality and diagnostic accuracy of 16-slice multidetector computed tomography for the detection of coronary artery disease in obese patients

Abstract: Background: Cardiac multislice spiral computed tomography (MSCT) scanners permit visualization of the coronary arteries with an overall good sensitivity (sens) and specificity (spec). However, in obese patients (pts), who are at higher risk to develop coronary artery disease (CAD), image quality of MSCT is supposed to be limited. At present, there are no data whether the accuracy of MSCT depends on the body mass index (BMI). Thus, we compared the catheter-controlled MSCT results from normal weight and obese pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…11,[15][16][17] One small retrospective study using older CCTA technology in 53 individuals aged Ͼ65 found that advancing age adversely affected image quality but did not hamper diagnostic accuracy. 16 Similarly, we identified 2 age groups (65 to Ͻ75 and Ն75 years) to carry escalating risk for obtaining Ն1 uninterpretable coronary segment by CCTA. Uninterpretable coronary segments are not universal in elderly persons, and even at the most advanced ages (Ͼ75 years), we found that Ͼ70% of individuals have all coronary segments interpretable.…”
Section: Age Heart Rate Cacs and Uninterpretable Coronary Segmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[15][16][17] One small retrospective study using older CCTA technology in 53 individuals aged Ͼ65 found that advancing age adversely affected image quality but did not hamper diagnostic accuracy. 16 Similarly, we identified 2 age groups (65 to Ͻ75 and Ն75 years) to carry escalating risk for obtaining Ն1 uninterpretable coronary segment by CCTA. Uninterpretable coronary segments are not universal in elderly persons, and even at the most advanced ages (Ͼ75 years), we found that Ͼ70% of individuals have all coronary segments interpretable.…”
Section: Age Heart Rate Cacs and Uninterpretable Coronary Segmentsmentioning
confidence: 99%
“…15,16 Control of heart rate and use of adequate rate-lowering techniques are important technical considerations to improve quality and results in CCTA. Similarly, future studies and predictive models that account for antecedent CACSs are needed and may provide tiered selection approach resource utilization in CCTA.…”
Section: Age Heart Rate Cacs and Uninterpretable Coronary Segmentsmentioning
confidence: 99%
“…One retrospective analysis of 117 patients in obese subjects found no statistical difference in CAD detection in normal weight, overweight, and obese patients when compared with conventional coronary angiography [29]. Despite this single trial, most radiologists believe that depth-dependent spatial resolution is worse with increasing torso size and weight restrictions on CT scanner tables (approximately 300-350 lbs in most cases) may limit the use of this imaging technique in some patients.…”
Section: Computed Tomographic Coronary Angiographymentioning
confidence: 88%
“…Initial studies reported sensitivity and specificity rates of 59% to 95% and 79% to 98%, respectively, primarily in patients with stable angina pectoris referred for cardiac catheterization ( Table 1). The rate of adequate visualization of coronary vessels in these studies ranged from 68% to 96% [18][19][20][21][22][23][24][25][26][27][28]. These results have compared favorably with other modalities such as intravascular ultrasound and cardiac magnetic resonance imaging [29,30] but are still inadequate.…”
Section: Technical Aspects Of Ct/mdctmentioning
confidence: 94%
“…One study found that although patients in the lowest body mass index (BMI) category had significantly higher-quality images, there were no differences in sensitivity and specificity among groups [20].Fifty percent of patients in the study of Raff et al had a BMI 30 kg/m 2 . For these patients, sensitivity and specificity dropped to 90% and 86%, respectively.…”
Section: Obesitymentioning
confidence: 97%